Environmental mastery mediates relationships between mindsets and well-being - John B. Nezlek; Marzena Cypryańska; Joanna Gutral (PLoS ONE, 2025)
Research on mindsets, the extent to which people believe that people can change (incrementalism) has found that incrementalism is positively related to success in various domains. One explanation for this relationship is that incrementalism is associated with a mastery orientation, which in turn is associated with success/achievement. The present study examined if the relationship between incrementalism and positive outcomes can be extended to include well-being, and if so, would a mastery orientation mediate such relationships. The present study examined if environmental mastery as conceptualized by Ryff and colleagues mediated relationships between mindsets and well-being. Participants (n = 447) completed measures of implicit theories of the self (incrementalism), Ryff and Keyes’s multidimensional measure of well-being, meaning in life, positivity, optimism, future time perspective, and self-esteem. A series of mediational analyses found that environmental mastery mediated relationships between incremental beliefs and all measures of well-being. For most measures of well-being, the direct effects of mindset beliefs on well-being were rendered non-significant when environmental mastery was included as a mediator. The present results confirm and extend to the general domain the supposition that a mastery orientation is responsible for relationships between well-being and incremental theories of the self.